Drug Use, Dependence, and Addiction at a British Columbia University: Good News and Bad News - Alexander, Bruce K. (Canadian Journal of Higher Education, 1985)
Two studies were undertaken to determine the perceived and actual prevalence of drug use, dependence, and addiction among students at Simon Fraser University. In thefirst, 144 students estimated the percentage of their fellow students that used each of seven drugs daily. Subsequently, each student reported how many days he or she had personally used each drug in the previous month. Estimated daily use (attributed tofellow students) was far higher than reported daily use. In a second study, detailed individual interviews of another group of students confirmed the unexpectedly low frequencies of daily use found in the first study: However, this does not mean that dependence and addiction were not a problem; of 107 students interviewed in the second study, 31% reported current dependence and about 5% current addiction. Surprisingly, the most common drugs in compulsive use were caffeine and nicotine followed, at a distance, by cannabis and alcohol. A new orientation towards drug problems among Canadian undergraduates in the 1980's is proposed, in which exaggerated concern over exotic, illicit drugs is replaced by greater awareness of serious problems of dependence and addiction to familiar drugs.